Approach to the patient with eosinophilia in the era of tyrosine kinase inhibitors and biologicals - Lübke, Johannes; Metzgeroth, Georgia; Reiter, Andreas; Schwaab, Juliana (Current hematologic malignancy reports, 2024)
In this review, we aim to explore the optimal approach to patients presenting with eosinophilia, considering recent advances in diagnostic and therapeutic strategies. Specifically, we focus on the integration of novel therapies into clinical practice to improve patient outcomes.
Online veröffentlicht: 22. Juli 2024
Gesehen am 20.11.2024